Effects of dietary lysolecithin on growth performance, feed utilization, intestinal morphology and metabolic responses of channel catfish (Ictalurus punctatus). (18th October 2019) - Liu, Guangxia; Ma, Shuoli; Chen, Feiyang; Gao, Weihua; Zhang, Wenbing; Mai, Kangsen
Abstract: This study investigated the effects of dietary lysolecithin on growth performance, feed utilization and metabolic responses of channel catfish ( Ictalurus punctatus ). Fish (initial weight: 14.77 ± 0.45 g) were randomly fed one of five practical diets supplemented with graded levels of lysolecithin (0, 125, 250, 375 and 500 mg/kg) in quadruplicate groups for 10 weeks. Results showed that no significant differences in weight gain, condition factor and viscerosomatic index among all the treatments. Fish fed diet supplemented with 250 mg/kg lysolecithin had significantly decreased feed conversion ratio and significantly increased protein efficiency ratio compared to that fed the control diet. The group with 250 mg/kg of dietary lysolecithin had higher protein and lower lipid contents in the whole body, and lower lipid content in the liver than those in the control group. Groups supplemented with 250–500 mg/kg of dietary lysolecithin had significantly higher gastric and intestinal lipase activities than the control group. Dietary lysolecithin at the level of 250 mg/kg significantly increased the activities of Na +, K + ‐ATPase, alkaline phosphatase, total antioxidative capacity, total superoxide dismutase, glutathione peroxidase and catalase and significantly decreased the content of malondialdehyde compared to the control diet. In conclusion, dietary supplementation of lysolecithin could confer benefits of feed utilization, body composition and antioxidative capacity of channel catfish.